Maternal variability of Croatian Spotted goat (Capra hircus) - Ivana Drzaic; Ino Curik; Dinko Novosel; Vlatka Cubric-Curik (Czech Journal of Animal Science, 2019)
Abstract: This study provides the first characterization of maternal ancestry and mitochondrial DNA (mtDNA) diversity in the Croatian Spotted goat (CSG), the most important autochthonous goat breed in Croatia. CSG (n = 25) were randomly sampled from seven herds and a 660-bp fragment from the mtDNA D-loop region was sequenced. Those sequences were compared with 122 corresponding GenBank sequences from goat populations in Albania, Austria, Egypt, Greece, Italy, Romania and Switzerland. CSG showed a great polymorphism (only three out of 17 haplotypes were shared) with high a haplotype (Hd = 0.967 ± 0.019) and nucleotide diversity (π = 0.01305 ± 0.00068). When compared with Mediterranean and ancient goats, all of the 25 CSG were randomly scattered inside haplogroup A showing the weak phylogeographic structure with within-breed variance accounting for 91.76% of the genetic variation. In addition, population expansion tests (mismatch distribution and Fu's Fs statistic) supported these results suggesting at least one population expansion.